Uso de adjuvantes (CAF 09, CAF 01 E MPL) mucosa-compatíveis na formulação de vacinas contra a leishmaniose viceral - Corea, Andrés Felipe Méndez (2018)
Visceral leishmaniasis is one of the endemic infectious-parasitic diseases in several countries, including Brazil, which affects humans and other vertebrates. Its treatment is made with specific drugs (pentavelentes antimonais, amphotericin B, pentamidines and miltefosina) of high toxicity, causing side effects in the patients, being thus a search for alternatives to control the disease is necessary. In this context, mucosal vaccines have been promising because of their specificity in the activation of the immune system associated with low cost and simple administration. The mucosal vaccination against visceral leishmaniasis, proposed by this study, uses a vaccine composed of total antigens of L. amazonensis (LaAg) in combination with adjuvants, such as CAF01, CAF09 and MPL, which are effective in generating a strong immune response by stimulating TLR1, 2, 4 and / or TLR 9. In this context, we evaluated the immunogenic and protective effects of intranasal administration of our vaccine in BALB / c mice challenged by L. infantum chagasi. Our results showed a promising response of the vaccine together with two adjuvants, CAF01 and MPL, leading to a decrease in the parasite load 60-fold and less in the case of the spleen and 30-fold less in the liver of the animals, as well as an increase in the expression of nitric oxide (80 μM) spleen and (150 μM) liver and also the presence of inflammatory cytokines ex-vivo IL-4 and IFN-γ. We also observed an increase in lymphoproliferation of CD8 + cells in splenocyte culture. Thus, we can determine the effectiveness of our base study vaccine in BALB / c mice.